2005
DOI: 10.1111/j.1399-3038.2005.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate allergic reactions to cephalosporins and penicillins and their cross‐reactivity in children

Abstract: Penicillins and cephalosporins are the most important betalactams inducing IgE-mediated reactions. The safety of administering cephalosporins to penicillin-allergic children is a particular problem, because cephalosporin allergenic determinants have not been properly identified. A study was undertaken to evaluate the frequency of anaphylactic reactions to cephalosporins and penicillins and their cross-reactivity in a pediatric population. A prospective survey was conducted in a group of 1170 children with susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
5
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 39 publications
(65 reference statements)
6
49
5
2
Order By: Relevance
“…In another study including ten patients with confirmed IgE-mediated allergy to cefazolin, cross-reactivity with penicillin was only detected in 10 % of cases [51]. In children, similar figures of cross-reactivity have been found, ranging from 0.3 to 23.9 %, with the figure being higher for earlier generation cephalosporins [53].…”
Section: Penicillin As An Alternative Treatmentsupporting
confidence: 54%
“…In another study including ten patients with confirmed IgE-mediated allergy to cefazolin, cross-reactivity with penicillin was only detected in 10 % of cases [51]. In children, similar figures of cross-reactivity have been found, ranging from 0.3 to 23.9 %, with the figure being higher for earlier generation cephalosporins [53].…”
Section: Penicillin As An Alternative Treatmentsupporting
confidence: 54%
“…163 For penicillin-allergic children, recent data suggest that cross-reactivity among penicillins and cephalosporins is lower than historically reported. [164][165][166][167] The previously cited rate of cross-sensitivity to cephalosporins among penicillin-allergic patients (approximately 10%) is likely an overestimate. The rate was based on data collected and reviewed during the 1960s and 1970s.…”
Section: Microbiologymentioning
confidence: 99%
“…7 More recent studies have demonstrated cross-reactivity rates as low as 1%. 8 The common beta-lactam ring is the putative reason for potential cross-reactivity between penicillins and cephalosporins.…”
Section: Beta-lactam Ringmentioning
confidence: 99%